2020
DOI: 10.1016/j.jsv.2020.115470
|View full text |Cite
|
Sign up to set email alerts
|

Important considerations in optimising the structural aspect of a SDOF electromagnetic vibration energy harvester

Abstract: This study investigates several important considerations to be made when optimising the structural aspects of a single-degree-of-freedom (SDOF) electromagnetic vibration energy harvester. Using the critically damped stress method, the damping and power output of the harvester were modelled and verified, displaying an excellent agreement with the experimental results. The SDOF harvester was structurally optimised under a certain set of constraints and it was found that under the fixed beam's thickness condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…These compromise solutions are obtained via a multiobjective optimization procedure. Recent studies related to this subject can be found in [23,24]. This solution highlights the effects of the combination of the nonlinearity and the energy localization on the performances of the proposed device.…”
Section: Theoretical and Experimental Approachesmentioning
confidence: 91%
“…These compromise solutions are obtained via a multiobjective optimization procedure. Recent studies related to this subject can be found in [23,24]. This solution highlights the effects of the combination of the nonlinearity and the energy localization on the performances of the proposed device.…”
Section: Theoretical and Experimental Approachesmentioning
confidence: 91%
“…Scholars have studied the motion of MFs in tuned magnetic fluid dampers (TMFDs) to enhance their energy consumption efficiency [54][55][56]. In recent years, an increasing number of vibration energy harvesters based on the levitation characteristics of ferrofluids have been developed to obtain electrical energy from low-frequency vibrations [57,58].…”
Section: Introductionmentioning
confidence: 99%
“…Vibration energy collection technology can effectively capture energy from the working environment of equipment and has developed rapidly in the past 20 years. At present, the common modes of vibration energy capture are piezoelectric [ 1 , 2 ], electromagnetic [ 3 , 4 ], triboelectric [ 5 ], and thermoelectric [ 6 ]. Among them, the piezoelectric energy harvesting device has the advantages of simple structure, high output voltage, wide working frequency range, and high energy density [ 7 , 8 , 9 ], Additionally, the electromagnetic energy harvesting device has the advantages of simple structure, large output current, and high energy collector efficiency [ 10 ].…”
Section: Introductionmentioning
confidence: 99%